2014
DOI: 10.4103/1463-1741.134919
|View full text |Cite
|
Sign up to set email alerts
|

Occupational hearing loss of market mill workers in the city of Accra, Ghana

Abstract: Noise induced hearing loss (NIHL) is an irreversible sensorineural hearing loss associated with exposure to high levels of excessive noise. Prevention measures are not well established in developing countries. This comparative cross sectional study aims to determine the prevalence of hearing loss in both a group of high risk workers and a control group and to assess their knowledge of the effects of noise on hearing health. A total of 101 market mill workers and 103 controls employed within markets in the city… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
27
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 12 publications
6
27
1
1
Order By: Relevance
“…Therefore, it is evident that more workers are being exposed to occupational harmful agents at their workplace. It is estimated that over 1,000 million people are employed in small-scale industries worldwide (2), many of whom come from developing countries where the state of occupational health and safety in small and medium-scale manufacturing industries is re-ally poor or not at the top of the health issues or policies (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is evident that more workers are being exposed to occupational harmful agents at their workplace. It is estimated that over 1,000 million people are employed in small-scale industries worldwide (2), many of whom come from developing countries where the state of occupational health and safety in small and medium-scale manufacturing industries is re-ally poor or not at the top of the health issues or policies (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…The destructive nature of excessive loud noise to high frequencies was very well studied. NIHL primarily affects the high frequencies region, such as 3 k, 4 k and 6 kHz and then spread to lower frequencies such as 0.5 k, 1 k and 2 kHz (Chen & Tsai 2003;Kitcher et al 2014;Maisarah 1993;Ologe et al 2006). Although at the moment we could not conclude that hearing loss experienced were NIHL, there is possibility that our respondents may suffer from NIHL since some of them do have some of the characteristics of NIHL.…”
Section: Discussionmentioning
confidence: 82%
“…In 2014, within the cotton ginning factories located in Parakou, noise level varied from 54 to 105.4 dB (A) among the workers investigated. In Ghana, Kitcher E. et al [14] reported in 2014 that condiment mill workers operating in markets were exposed to ambient noise levels ranging from 85.9 to 110.8 dB (A). Every year, 22 million workers are exposed to dangerous noise or sound levels in the United States [15].…”
Section: Discussionmentioning
confidence: 99%
“…In Africa, there are few data on the prevalence of NIHL at work place [18]. In Ghana, Kitcher et al [14] had found in 2014 twentyfour decimal eight percent (24.8%) of hearing loss among condiment mill workers operating in markets. In Nigeria, Ologe et al [19] had found in 2006 among 103 workers of a rolling mill exposed to noise levels ranging from 49 to 93 dBA; nearly 28.2% of people presented with sensorineural hearing loss in their best ear and 56.8% presented with sensorineural hearing loss in their worse ear.…”
Section: Discussionmentioning
confidence: 99%